AI Adoption For Accelerating Tourism Destination Development In Indonesia - Eko Susanto; Bintari Pangesti Putri; Mega Fitriani Adiwarna Prawira; Chandrawulan (Journal of Tourism, Hospitality and Travel Management, 2025)
Artificial Intelligence (AI) is increasingly transforming tourism by enabling personalised experiences, optimising operations, and supporting sustainable destination development. While extensive research has explored AI applications in advanced economies, studies remain limited in emerging contexts such as Indonesia. Addressing this gap, this study investigates how AI adoption can accelerate tourism destination development in Indonesia, a country with rich natural and cultural assets but significant digital, infrastructural, and governance challenges. Employing a qualitative strategic management approach, this study integrates SWOT–TOWS analysis and expert panel validation to identify internal and external factors influencing AI readiness. The findings position Indonesia in the Strength–Opportunity (SO) quadrant, suggesting that AI technologies—such as recommendation systems, virtual storytelling, and predictive analytics—hold significant potential for destination differentiation and sustainability. However, persistent barriers include low AI literacy, fragmented data systems, and regulatory limitations. The study contributes theoretically by contextualizing Innovation Diffusion Theory and Smart Tourism frameworks within a developing economy. Practically, it offers a strategic roadmap for inclusive and ethical AI adoption in tourism. Future research should explore quantitative modeling, cross-country comparisons, and the development of tourism-specific AI governance frameworks.